Sharing responsibility: jeopardised multilateralism and the growing centrality of Triangular Cooperation - Geovana Zoccal (Revista Brasileira de Política Internacional, 2020)
Abstract Multipolarity is casting doubt on the notion of responsibility, and diffused reciprocity of the multilateral system of international development cooperation is falling short. In midst of this crisis, what are possible mechanisms to foster the implementation of the 2030 Agenda? I argue that Triangular Cooperation, through specific reciprocity, presents opportunity for nurturing partnerships and enhancing models to share responsibilities toward international development cooperation. Looking into recent trends of TrC, I argue that through this modality, DAC countries push for greater involvement of the South, and Southern providers share responsibility towards international development.